Factors influencing early recurrence of atrial fibrillation among elderly patients following radiofrequency catheter ablation and the impact of different antiarrhythmic regimens - Fei, Changdong; Zhao, Caitong; Ma, Yan; Liu, Yupeng; Chen, Renzheng; Zhang, Hualin (Frontiers in Medicine, 2024)
Background: Patients with atrial fibrillation (AF) who undergo radiofrequency catheter ablation (RFCA) necessitate the administration of antiarrhythmia drugs to prevent early recurrence. The clinical outcomes among these patients may be influenced by varying antiarrhythmia regimens. Objectives: To identify the risk factors associated with early recurrence and compare the clinical outcomes among different antiarrhythmia regimens in elderly patients with AF following radiofrequency catheter ablation (RFCA) during a 3-month period. Methods: A retrospective observational study encompassed 420 elderly patients with AF following RFCA. Baseline data were collected during the initial postoperative visit. and clinical outcomes were carefully monitored over a 3-month follow-up period. Logistic regression and Coxproportional hazard regression analyses were performed to investigate the relationship between various antiarrhythmia regimens and the clinical outcomes.Results: Multivariate logistic regression analysis revealed that age (p=0.001), left atrial diameter (p<0.001), left ventricular diameter (p=0.015), reactive hyperemia index (RHI) (p<0.001), antiarrhythmic drug (p<0.001) and hs-cTnI (p=0.017) were independent risk factors of early recurrence. Furthermore, in cox survival regression analysis model, survival rate of early recurrence in the amiodarone group was higher than in the propafenone group (HR 2.30, p=0.016) and in the sotalol group (HR 3.60, p<0.001). Compared to the amiodarone group, the incidence of liver dysfunction was lower in the dronedarone group (p=0.046) and the propafenone group (p=0.021). The incidence of bradyarrhythmia (p=0.003), QT interval prolongation (p=0.035) and atrioventricular transmission block (p=0.021) were higher in the sotalol group than in the amiodarone group.Conclusions: RHI was identified as an independent risk factor for early recurrence among elderly AF patients after RFCA. Compared to amiodarone, propafenone and sotalol exhibited an elevated risk of early recurrence. Although there was no significant difference in early recurrence between amiodarone and dronedarone, dronedarone emerged as the preferred option due to its lower frequency of adverse drug reactions than amiodarone.